Basım işletmelerinde yalın yönetim ve üretimin uygulanması - Kırmızıoğlu, Filiz (My University, 2022)
BASIM İŞLETMELERİNDE YALIN YÖNETİM VE ÜRETİMİN UYGULANMASI Yalın üretim 1950 yılında Taichi Onho ve Eiji Toyoda’nın Fordist üretim sistemini inceleyerek daha deneyimli olan rakiplerle nasıl baş edeceklerini ortaya koymak için geliştirdikleri bir metodoloji felsefesidir. Geliştirdikleri felsefe kendi işletmelerinden başlayarak zamanla ülke çapında bir katma değere dönüşmüş ve küresel çapta uygulayıcılarını bulmuştur. Felsefenin temel amacı süreçlerdeki israfları tespit edip bunları değere dönüştürmektir. Değer dönüşümünü gerçekleştirebilmek için birtakım yalın teknik ve araçlar bulunmaktadır. Bu araçların tespiti için yalın düşüncenin ilkeleri ve değerleri anlaşıldıktan sonra mevcut üretim şeklinin (kitlesel üretim) sorunları tespit edilerek yalın dönüşüm adımları atılmalıdır. Yapılan uygulama çalışması ile klasik yöntemle yönetim ve üretimini sürdüren bir basım işletmesinin yalın yönetim ve üretime geçiş için yaptığı çalışma ve analizleri ile bazı yalın araçların uygulanışı verilmiştir. İncelenen yalın teknik ve araçlar arasında Kaizen, Kanban, 5S, Gemba, Tam Zamanında Üretim, Toplam Üretken Bakım bulunmaktadır. Bu tekniklerin uygulama çalışmaları yapılmadan önce işletmenin yalın yönetim tarzına yatkınlığını anlamak ve işletme yapısını tanımak için Swot Analizi, Temel Yetkinlik Analizi ve Kurumsal Yaşam Döngüsü Analiz’i yapılmıştır. İşletmenin yalın yönetim analizinin ardından yalın yönetim ve üretimin uygulanabilirliğine yönelik çalışan anketi yapılmıştır. Yapılan analizler ve anket sonucunda işletmenin ideal yalın yönetim evresi belirlenmiş, işletmenin belirlenen sorunlarına uygun olan tekniklerle yalın çalışma uygulama basamakları oluşturulmuştur. Oluşturulan çalışma basamaklarının gerekli noktalarda uygulanmasıyla birlikte işletmenin Puan-Hedef Göstergeleri ile yalın değerlendirmesi yapılmıştır. Bu çalışmada uygulama yapılan işletmeden yola çıkılarak basım işletmelerinde yalın uygulamalar, yalın felsefe anlayışı, yalın ilkeleri ve yöntemleri, yönetim liderliği ve bağlılığı, verimli çalışan, sürdürülebilir çalışma süreçleri, yalın ve etkili iletişim için başarı ve başarısızlık faktörleri tanımlanmaya çalışılmış ve önerilerde bulunulmuştur. Lean manufacturing is a methodology philosophy developed by Taichi Onho and Eiji Toyoda in 1950 to examine the Fordist production system and reveal how to deal with more experienced competitors. The philosophy they developed, starting from their own businesses, has turned into a nationwide added value over time and has found its practitioners on a global scale. The main purpose of philosophy is to identify wastes in processes and turn them into value. There are some lean techniques and tools to realize the value transformation. In order to determine these tools, after understanding the principles and values of lean thinking, the problems of the current production style (mass production) should be identified and lean transformation steps should be taken. With the application study, the studies and analyzes of a printing company that continues its management and production with the classical method for the transition to lean management and production and the application of some lean tools are given. Lean techniques and tools reviewed include Kaizen, Kanban, 5S, Gemba, Just-In-Time Production, Total Productive Maintenance. Before applying these techniques, Swot Analysis, Basic Competency Analysis and Corporate Life Cycle Analysis were conducted to understand the lean management style of the enterprise and to recognize the business structure. After the lean management analysis of the enterprise, an employee survey was conducted on the applicability of lean management and production. As a result of the analyzes and the survey, the ideal lean management phase of the enterprise was determined, and lean working application steps were created with the techniques suitable for the determined problems of the enterprise. With the application of the created work steps at the necessary points, a lean evaluation of the enterprise was made with the Score-Target Indicators. In this study, success and failure factors for lean practices, lean philosophy understanding, lean principles and methods, management leadership and commitment, efficient working, sustainable working processes, lean and effective communication in printing businesses were tried to be defined and suggestions were made, starting from the company where the application was made.

Lean manufacturing is a methodology philosophy developed by Taichi Onho and Eiji Toyoda in 1950 to examine the Fordist production system and reveal how to deal with more experienced competitors. The philosophy they developed, starting from their own businesses, has turned into a nationwide added value over time and has found its practitioners on a global scale. The main purpose of philosophy is to identify wastes in processes and turn them into value. There are some lean techniques and tools to realize the value transformation. In order to determine these tools, after understanding the principles and values of lean thinking, the problems of the current production style (mass production) should be identified and lean transformation steps should be taken. With the application study, the studies and analyzes of a printing company that continues its management and production with the classical method for the transition to lean management and production and the application of some lean tools are given. Lean techniques and tools reviewed include Kaizen, Kanban, 5S, Gemba, Just-In-Time Production, Total Productive Maintenance. Before applying these techniques, Swot Analysis, Basic Competency Analysis and Corporate Life Cycle Analysis were conducted to understand the lean management style of the enterprise and to recognize the business structure. After the lean management analysis of the enterprise, an employee survey was conducted on the applicability of lean management and production. As a result of the analyzes and the survey, the ideal lean management phase of the enterprise was determined, and lean working application steps were created with the techniques suitable for the determined problems of the enterprise. With the application of the created work steps at the necessary points, a lean evaluation of the enterprise was made with the Score-Target Indicators. In this study, success and failure factors for lean practices, lean philosophy understanding, lean principles and methods, management leadership and commitment, efficient working, sustainable working processes, lean and effective communication in printing businesses were tried to be defined and suggestions were made, starting from the company where the application was made.
Implementation of lean management and production in printing businesses
Keywords: Basım; BASIM İŞLETMELERİ VALUE; DEĞER; EFFICIENCY; İSRAF; LEAN; PRINTING ENTERPRISES; Printing; Technology; Teknoloji; VERİMLİLİK; WASTE; YALIN